A 16-gene assay to predict recurrence after surgery in localised renal cell carcinoma: development and validation studies. Issue 6 (June 2015) - Rini, Brian; Goddard, Audrey; Knezevic, Dejan; Maddala, Tara; Zhou, Ming; Aydin, Hakan; Campbell, Steven; Elson, Paul; Koscielny, Serge; Lopatin, Margarita; Svedman, Christer; Martini, Jean-Francois; et al.
Summary: Background: The likelihood of tumour recurrence after nephrectomy in localised clear cell renal cell carcinoma is well characterised by clinical and pathological parameters. However, these assessments can be improved and personalised by the addition of molecular characteristics of each patient's tumour. We aimed to develop and validate a prognostic multigene signature to improve prediction of recurrence risk in clear cell renal cell carcinoma. Methods: In the development stage, we investigated the association between expression of 732 genes, measured by reverse-transcription PCR, and clinical outcome in 942 patients with stage I–III clear cell renal cell carcinoma who had undergone a nephrectomy at the Cleveland Clinic (OH, USA). 516 genes were associated with recurrence-free interval. 11 of these genes were selected by further statistical analyses, and were combined with five reference genes (ie, 16 genes in total), from which a recurrence score algorithm was developed. The recurrence score was then validated in an independent cohort of 626 patients from France with stage I–III clear cell renal cell carcinoma who had also undergone nephrectomy. The association between the recurrence score and the risk of recurrence and cancer-specific survival in the first 5 years after surgery was assessed using Cox proportional hazard regression, stratified by tumour stage (stage I vs stage II vs III). Findings: In our primary univariate analysis, the continuous recurrence score (median 37, IQR 31–45) was significantly associated with recurrence-free interval (hazard ratio 3·91 [95% CI 2·63–5·79] for a 25-unit increase in score, p<0·0001). In multivariable analyses, the recurrence score was significantly associated with the risk of tumour recurrence (hazard ratio per 25-unit increase in the score 3·37 [95% CI 2·23–5·08], p<0·0001) after stratification by stage and adjustment for tumour size, grade, or Leibovich score. The recurrence score was able to identify a clinically significant number of both high-risk stage I and low-risk stage II–III patients. A heterogeneity study on separate samples showed little to no intratumoural variability among the 16 genes. Interpretation: Our findings validate the recurrence score as a predictor of clinical outcome in patients with stage I–III clear cell renal cell carcinoma, providing a more accurate and individualised risk assessment beyond existing clinical and pathological parameters. Funding: Genomic Health Inc and Pfizer Inc.